Rotavirus type profile in nosocomial and community infections in Western Slovakia - Štefkovičová, M; Litvová, S; Šimurka, P; Göczeová, J; Gajdošíková, A; Krištúfková, Z (Folia microbiologica, 2015)
The surveillance study of rotavirus gastroenteritis at the University Teaching Hospital Trenčín area, Slovakia, during 2006-2011 confirmed that the genotype profile of circulating rotaviruses was not stable. While G1P[8] dominating genotype dropped from 75 to 7.3 % in the period 2009-2011, genotype G2P[4] that was not detected in 2009 raised to 45.1 % in 2011. Vaccination coverage rose from 4.4 to 22.1 % in the period 2008-2011. Among the community and hospital cases, we observed that the average age of patients with nosocomial infections was significantly less (10.6 months) than in the cases of community rotavirus gastroenteritis (RVGE) cases. Compared to the nosocomial infection cases, the duration of the disease and the duration of hospitalization among the community cases were significantly longer by 0.22 and 3.63 days, respectively, during 2006-2011. Though the vaccination coverage was found to correlate with changes in the type of the circulating rotaviruses, the natural circulation in rotavirus genotypes may not be excluded as important factor contributing to the emergence of G2P[4] strain during the survey period.
Keywords: Rotavirus; Slovakia; molekulární epidemiologie; Slovenská republika; infekce spojené se zdravotní péčí; Rotavirus Infections; gastroenteritida; Humans; genotyp; Cross Infection; Molecular Epidemiology; Genotype; rotavirové infekce; lidé; Gastroenteritis; infekce získané v komunitě; Community-Acquired Infections